FINANCIAL LITERACY AMONG HOUSEWIVES TO MANAGE CONSUMPTION PATTERNS AFTER PANDEMIC COVID-19 - Dessy Harisanty; Dyah Puspitasari Srirahayu; Esti Putri Anugrah; Muhammad Rifky Nurpratama (Publication Library and Information Science, 2022)
The COVID-19 pandemic has now been running for about 3 years, many community activities are spent at home, bringing new habit patterns for them. One of them is shopping online, since the time of the pandemic people are very accustomed to online shopping patterns. The solution to be able to provide advice on the consumption patterns of consumptive citizens is the introduction of financial literacy, especially through education programs and training on saving habits. This study aims to describe the financial literacy of housewives so that consumer activities can be controlled. The method used in this research is quantitative descriptive, the location of this research is at Plandaan Village, Kedungwaru District, Tulungagung Regency. To determine the sample using a non-random sampling technique that is purposive sampling. The total respondents in this study were 50 housewives. Result of this study shows that housewives have a good general knowledge of personal finance, and have sufficient Savings, Loans, and Investments.Â Â Many housewives have funds for emergency needs, so they don't experience confusion when something sudden happens.